2011
DOI: 10.1074/jbc.m111.281394
|View full text |Cite
|
Sign up to set email alerts
|

EPI64 Protein Functions as a Physiological GTPase-activating Protein for Rab27 Protein and Regulates Amylase Release in Rat Parotid Acinar Cells

Abstract: Rab27, a small GTPase, is generally recognized as an important regulator of secretion that interacts with Rab27-specific effectors to regulate events in a wide variety of cells, including endocrine and exocrine cells. However, the mechanisms governing the spatio-temporal regulation of GTPase activity of Rab27 are not firmly established, and no GTPase-activating protein (GAP) specific for Rab27 has been identified in secretory cells. We previously showed that expression of EPI64, a Tre-2/Bub2/ Cdc16 (TBC)-domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 55 publications
(84 reference statements)
1
21
1
Order By: Relevance
“…EPI64 also functions as a Rab27a GAP through its Tre-Bud-Cdc16 (TBC) domain Imai et al, 2011). We have recently shown that glucose induces the conversion of GTP-bound Rab27a into its GDP-bound form through EPI64 in pancreatic β-cells (Kimura et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…EPI64 also functions as a Rab27a GAP through its Tre-Bud-Cdc16 (TBC) domain Imai et al, 2011). We have recently shown that glucose induces the conversion of GTP-bound Rab27a into its GDP-bound form through EPI64 in pancreatic β-cells (Kimura et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…However, Rab3GAP was identified as specific for Rab3 subfamily members (44). A recent study has demonstrated that EPI64/ TBC1D10A can serve as a physiological GAP for Rab27A in parotid acinar cells and regulate amylase release (45). We verified the expression of EPI64 and EPI64B in isolated pancreatic acini by RT-PCR and EPI64B by Western blotting and then made epitope-tagged EPI64 and EPI64B adenoviruses.…”
Section: Discussionmentioning
confidence: 90%
“…A recently published study showed that inhibition of EPI64, either by antibody or antisense locked nucleic acid, reduced amylase release from parotid acinar cells (45). It has also been reported that in pancreatic acini, knockout of Slp1, a downstream effector of Rab27B, increased both the numbers of zymogen granules and amylase secretion in fasted mice (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a homologue of EPI64, EPI64B also exhibited Rab27A GAP activity in vitro. EPI64 is a physiological GAP for Rab27 in rat parotid acinar cells and down-regulation of EPI64 caused a reduction in the amount of amylase release (33). A recent study showed that EPI64 also functions as Rab27A specific GAP in a lung adenocarcinoma cell line and regulates exosome secretion.…”
Section: Rab27amentioning
confidence: 99%